Finite predicates method for assessment of anthropogenic effect - O. M. Bakunova; V. M. Abraztsova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The method of complex assessment of anthropogenic effect on the territory units is suggested. Particular indications taken as the basic of complex assessment correspond to the «Environmental Indicators and Indicators-based Assessment Reports - Eastern Europe, Caucasus and Central Asia» (ECE/CEP/140) [1]. On the basis of these data complex indicator is obtained in accord with the method of finite predicates. This indicator characterizes the contamination level of the environment on particular area as well as comfort of living in the area.